Passivation of Germanium Surfaces by HF:H2O2 Aqueous Solution - Terletskaia, Mariia; Isometsä, Joonas; Miettinen, Mikko; Laukkanen, Pekka; Vähänissi, Ville; Savin, Hele (WILEY-V C H VERLAG GMBH, 2025)
Promising intrinsic electronic properties, such as narrow bandgap and high charge carrier mobilities, make germanium (Ge) a good replacement for silicon in optoelectronic applications (e.g., photodetectors). However, successful fabrication of efficient Ge devices requires minimization of both reflectance and surface recombination losses. This work begins with an observation that metal-assisted chemical etching (MACE) of Ge surfaces, used for optics improvement, reduces surface recombination without application of any intentional passivation. We proceed with investigation of the effect of MACE solution components and their mixtures on Ge surface passivation. The results demonstrate that HF:H2O2 aqueous solution leads to efficient and stable passivation. The film formed in this solution secures surface recombination velocity (Seff) of 14 cm s-1. Morphological and chemical characterization of the structure reveals porous germanium (PGe) layer with some GeOx included. Finally, we propose several hypotheses on a mechanism behind this passivation, among which are the presence of GeO2 at the film-bulk Ge interface and appearance of a potential barrier due to the heterojunction formation. The presented Ge passivation with PGe layer provides a simple and cost-efficient alternative to existing state-of-the-art passivation schemes.